Self-Assembled Thermoresponsive Polymeric Nanogels for 19F MR Imaging - Kolouchova, Kristyna; Sedlacek, Ondrej; Jirak, Daniel; Babuka, David; Blahut, Jan; Kotek, Jan; Vit, Martin; Trousil, Jiri; Konefał, Rafał; Janouskova, Olga; Podhorska, Bohumila; Slouf, Miroslav; et al. (Biomacromolecules, 2018)
Magnetic resonance imaging using fluorinated contrast agents (19F MRI) enables to achive highcontrast in images due to the negligible fluorine background in living tissues. In this pilot study, we developed new biocompatible, temperature-responsive, and easily synthesized polymeric nanogels containing a sufficient concentration of magnetically equivalent fluorine atoms for 19F MRI purposes. The structure of the nanogels is based on amphiphilic copolymers containing two blocks, a hydrophilic poly[ N-(2-hydroxypropyl)methacrylamide] (PHPMA) or poly(2-methyl-2-oxazoline) (PMeOx) block, and a thermoresponsive poly[ N(2,2difluoroethyl)acrylamide] (PDFEA) block. The thermoresponsive properties of the PDFEA block allow us to control the process of nanogel self-assembly upon its heating in an aqueous solution. Particle size depends on the copolymer composition, and the most promising copolymers with longer thermoresponsive blocks form nanogels of suitable size for angiogenesis imaging or the labeling of cells (approximately 120 nm). The in vitro 19F MRI experiments reveal good sensitivity of the copolymer contrast agents, while the nanogels were proven to be noncytotoxic for several cell lines.
Keywords: kyseliny polymethakrylové; Animals; HeLa Cells; Magnetic Resonance Imaging; polyethylenimin; fluor; Nanogels; teplota; Polyamines; Polyethylene Glycols; hemolýza; Polyethyleneimine; Fluorine; lidé; HeLa buňky; Mice; magnetická rezonanční tomografie; Polymerization; kultivované buňky; myši; Polymethacrylic Acids; polyethylenglykoly; Temperature; Cells, Cultured; kontrastní látky; nanogely; Hemolysis; polymerizace; zvířata; Contrast Media; polyaminy; Humans